UPAYA MENINGKATKAN KUALITAS BOKASHI MELALUI PEMBERIAN CANGKANG TELUR, ABU DAPUR, DAN URINE SAPI SERTA PENERAPANNYA DALAM BUDIDAYA SAWI SECARA ORGANIK - Lena Walunguru; Aloysius Ng. Lende (Politeknik Pertanian Negeri Kupang, 2008)
Increasing Quality of Bokashi by Apply Eggshell Powder, Ash, and Cow Urine and Application in Cultivation of Organic Mustard Green. The research aimed to know quality of bokashi added eggshell powder, ash, and cow urine to plant productivity.The research used Completely Randomized Block Design consisting ofÂ eight treatments were bokashi (B0), bokashi added eggshell powder (B1), bokashi added ash (B2), bokashi added cow urine (B3), bokashi added eggshell powder and ash (B4), bokashi added eggshell powder and cow urine (B5), bokashi added ash and cow urine (B6), and bokashi added eggshell powder, ash, and cow urine. The data was anayzed by using Analysis of Variance and Honestly Significant Difference (HSD) at 5%. The result showed that bokashi without nutrient increasing matter have 0,49% amount of N plant tissue, if bokashi added eggshell powder or ash the amount of N plant tissue 0,51%. Bokashi added cow urine significant to increasing wet plant weigh amount 24,49%. Bokashi added ash, bokashi added eggshell powder and cow urine, bokashi added ash and cow urine, significant to increasing wet plant weigh each 20,22%, 26,04%, and 26,80%. Dry plant weigh signicant increasing amount 30% and 32,22% if bokashi added eggshell powder and bokashi added ash. Key words: bokashi, quality, organic mustard green